2021
DOI: 10.3389/fgene.2021.707299
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer Associated Immune Genes as Biomarkers for Predicting Outcome in Upper Gastrointestinal Tumors

Abstract: Esophageal cancer (EC) is the seventh most common tumor in the world, ranking the sixth leading cause of cancer death, with a 5-year survival rate of 15-25%. Therefore, reliable prognostic biomarkers are needed to effectively predict the prognosis of EC. In this study, the gene profile information of the EC cohort served as a training set, which was derived from TCGA and Immport databases. GO and KEGG enrichment analysis was performed on the differential genes in normal and tumor groups of EC. The immune genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…STC2 was also identified as an interacting partner of the plasma-protein histidine-rich glycoprotein, regulating glioma growth through the modulation of antitumor immunity [ 32 ]. Regarding ESCC, some bioinformatic studies strongly suggested that STC2 was a potential prognostic biomarker without further validation [ [33] , [34] , [35] ]. One study explored and validated that STC2 showed higher expression in ESCC tissues than in corresponding normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…STC2 was also identified as an interacting partner of the plasma-protein histidine-rich glycoprotein, regulating glioma growth through the modulation of antitumor immunity [ 32 ]. Regarding ESCC, some bioinformatic studies strongly suggested that STC2 was a potential prognostic biomarker without further validation [ [33] , [34] , [35] ]. One study explored and validated that STC2 showed higher expression in ESCC tissues than in corresponding normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dai et al, developed an eleven-gene prognostic model that showed good performance for prognosis prediction [32]. Zhu et al, reported a six-gene signature for predicting OS [33]. Although there is growing evidence that tumor immune phenotypes are signi cantly associated with prognosis and treatment response in various types of cancer, few studies have focused on the genetic signature of key genes of the tumor immune microenvironment based on immune-associated lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…A multivariate Cox regression analysis demonstrated that VEGFA, age, and grade were still the significant increasing risk factor (Figure 3F). Nomograms are widely used for prognostic assessment of tumors, which simplify statistical prediction models to single numerical estimates of event probabilities tailored to individual patient profiles (23). A 1-year nomogram indicated that there are three components of this nomogram: VEGFA, age, and grade (Figure 3G).…”
Section: Vegfa As a Key Regulator Of Angiogenesis Is An Important Pro...mentioning
confidence: 99%